2011
DOI: 10.1016/j.ijnonlinmec.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Load carrying capacity of systems within a global safety perspective. Part II. Attractor/basin integrity under dynamic excitations

Abstract: . Load carrying capacity of systems within a global safety perspective Part II. Attractor/basin integrity under dynamic excitations. International Journal of Non-Linear Mechanics, Elsevier, 2011, 46 (9) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In fact, only the basic aspect of the dynamical integrity perspective, which consists of allowing for finite size perturbations, has been used in this paper, since it is sufficient for highlighting the actual robustness of stable equilibria. As it will be shown in Part II of this work [17], the issue of system load carrying capacity and global safety in the presence of actual dynamic excitations requires full consideration of its highly variable dynamic response, with the ensuing effects in terms of reduction of dynamical integrity due to the erosion phenomena entailed by the possible occurrence of fractal basins of attraction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, only the basic aspect of the dynamical integrity perspective, which consists of allowing for finite size perturbations, has been used in this paper, since it is sufficient for highlighting the actual robustness of stable equilibria. As it will be shown in Part II of this work [17], the issue of system load carrying capacity and global safety in the presence of actual dynamic excitations requires full consideration of its highly variable dynamic response, with the ensuing effects in terms of reduction of dynamical integrity due to the erosion phenomena entailed by the possible occurrence of fractal basins of attraction.…”
Section: Discussionmentioning
confidence: 99%
“…the finite magnitude of the area of the safe basin) is not enough to guarantee the real dynamical integrity of the system, as it will be clarified in Part II of this work [17]. However, it is a sufficient concept for the goal pursued herein.…”
Section: Global Safety or The Thompson Critical Loadmentioning
confidence: 95%
See 2 more Smart Citations
“…In [28], it is shown that the requirement of a large basin also applies in the absence of dynamical excitation, because close to the static bifurcation point the basin of attraction shrinks to zero and thus the associated equilibrium point is no longer robust, the situation being unsafe. In [29], on the other hand, the dynamical excitation is added, and the interactions between the excitation amplitude and the axial load in reducing the global safety are investigated, analysing in-depth both the basin extent and its compactness.…”
Section: Introductionmentioning
confidence: 99%